2020
DOI: 10.47392/irjash.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Discussion for Improving Motivation: A Christian Education Strategy against Covid-19 Pandemic Effect

Abstract: There was a big question about the transition to online learning on around the world, could it motivate student as good as the traditional methods? This study is aimed at finding out the effectiveness of virtual discussion for improving motivation of students during the Covid-19 pandemic. A total of sixty Christian students of State Vocational High School Malang were involved in the study, separated in two classes. The first class was treated with virtual discussion method and the other class as a control clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Online learning is effective in motivating students to learn, including interactive eBooks [13]. During the COVID-19 pandemic, online learning can be done with the virtual discussion method and this method is effective in increasing student motivation [33].…”
Section: Overall Results Categorized By Research Questionsmentioning
confidence: 99%
“…Online learning is effective in motivating students to learn, including interactive eBooks [13]. During the COVID-19 pandemic, online learning can be done with the virtual discussion method and this method is effective in increasing student motivation [33].…”
Section: Overall Results Categorized By Research Questionsmentioning
confidence: 99%
“…Positive social relationships will help children to develop so that it affects children's cognitive. Loving parenting can also improve a child's cognitive development (Ariawan et al, 2020). Educators need to understand that every student is born with different potentials and is carried from birth.…”
Section: Resultsmentioning
confidence: 99%
“…Cooperative skills consisted of In cooperative learning there were six steps or stages, where learning began with the teacher conveyed learning objectives and motivated students to learn [7]. Further grouped in the learning teams, followed the guidance of teachers at the time students collaborated to complete the task and the last presentation of the group's work [8]. Phases in cooperative learning as below: Based on the exposure described above about the learning outcomes, it could be concluded that the learning results consisted of three things: cognitive, affective, and psychomotor [11].…”
Section: Implementing Cooperative Learningmentioning
confidence: 99%